Prospects for Covenantal Pluralism in the People's Republic of China: A Reflection on State Policy and Muslim Minorities - Wang, Yuting (The review of faith & international affairs, 2021)
By focusing on the Chinese state's shifting policies toward Islam and its Muslim minorities, this article considers the possibilities of implementing covenantal pluralism in contemporary China. While the current socio-political conditions in China hold little promise for the realization of covenantal pluralism, there are important social and cultural sources that may be leveraged to reorient the state policy toward a more pluralistic future. This article suggests that to put down roots in China and elsewhere, covenantal pluralism must acknowledge and address the political and economic hierarchy in the world system, which are unlikely to relinquish in the foreseeable future.